Impact of CD4 count in the development of mycobacterium tuberculosis in patients with HIV infection in a tertiary care centre - T. B., Satyanarayan; M. P., Manjunath; M., Ranganath; M., Mahendra (International Journal of Advances in Medicine, 2018)
Background: Patients with Human Immunodeficiency Virus (HIV) infection are predisposed to numerous opportunistic infections due to decreased cell mediated immunity, Tuberculosis being most common. Low CD4 count is associated with low immunity and higher risk of tuberculosis. Methods: Author conducted a retrospective study in the department of Pulmonary medicine in a tertiary care teaching hospital during January to December 2017. Author collected data of all the patients with HIV diagnosed with Tuberculosis from the ART centre. Author collected demographic details including age, sex, symptoms at presentation, details of diagnosis of TB including type of tuberculosis, CBNAAT results, CD4 count at the diagnosis of TB, details of ART therapy and ATT therapy and outcomes of treatment. Results: Eighty one patients with HIV-TB co- infection were included in the study. Males (70.37%) were more affected than females. Mean age of the study group was 39.97±10 years. Sixty one patients (75.4%) were diagnosed with Pulmonary Tuberculosis and 20 (24.6%) patients were diagnosed with extra pulmonary TB. Mean CD4 counts of the cohort was 226±110/µl. Eighty percent of patients developed Tuberculosis with CD4 count <250/µl. Conclusions: Author found in this study higher proportions of tuberculosis (80.2%) in patients with HIV infection with CD4 count <200/µl. Author also found higher proportion of pulmonary Koch’s in patients with low CD4 count (CD4 <200/µl).